2019
DOI: 10.1176/appi.ps.201800321
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use and Misuse Among Adults in the United States

Abstract: Objective: Determine the prevalence of benzodiazepine use, including both use as-prescribed and misuse; characterize misuse; determine whether and how misuse varies by age. Methods: Cross-sectional analysis of the 2015 and 2016 National Survey on Drug Use and Health (NSDUH), a nationally-representative sample of U.S. adults (n=86,186). Measurements included past-year prescription benzodiazepine use and misuse (i.e., use "any way a doctor did not direct"), along with substance use and use disorders, mental illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
162
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(185 citation statements)
references
References 40 publications
13
162
0
10
Order By: Relevance
“…Recent epidemiological studies report a steep rise in benzodiazepine misuse and overdose mortality, occurring most commonly in poly drug users (Dunbar et al, 1988;Woods et al, 1992;Griffiths and Weerts, 1997;Lekka et al, 1997;Neutel, 2005;Licata and Rowlett, 2008;Bachhuber et al, 2016;Lembke et al, 2018;Maust et al, 2019). We showed that nicotine pretreatment increases diazepam intake for several days.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recent epidemiological studies report a steep rise in benzodiazepine misuse and overdose mortality, occurring most commonly in poly drug users (Dunbar et al, 1988;Woods et al, 1992;Griffiths and Weerts, 1997;Lekka et al, 1997;Neutel, 2005;Licata and Rowlett, 2008;Bachhuber et al, 2016;Lembke et al, 2018;Maust et al, 2019). We showed that nicotine pretreatment increases diazepam intake for several days.…”
Section: Discussionmentioning
confidence: 57%
“…Among the different classes of GABA A R-targeting drugs, benzodiazepine misuse is a growing public health problem in the United States, with prescription rates and overdose mortality spiking in recent years (Bachhuber et al, 2016;Lembke et al, 2018;Maust et al, 2019). Acting through positive allosteric modulation of GABA A R, benzodiazepines are regularly prescribed for panic attacks, insomnia, and seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Salienta-se também que esta comunicação não deva se dar somente ao serviço de psicologia / saúde mental na vigência de admissão de paciente que necessite desta atenção, mas a toda equipe interdisciplinar, visto que o paciente é atendido por profissionais de diversas categorias. Portanto, a necessidade de um protocolo diferenciado que oriente este cuidado é mandatória, pois o portador de transtorno mental na fase aguda encontrase numa situação de vulnerabilidade, por apresentar alteração do nível de consciência e consequente dificuldade na comunicação (9,16,(19)(20) .…”
Section: Discussionunclassified
“…A maior barreira descrita, com 10 respostas (52,6%), foi o nível de consciência / orientação deste paciente, pois o mesmo não é colaborativo, demonstra agressividade por conta da sua própria condição patológica (9,16,(19)(20) .…”
Section: Discussionunclassified
See 1 more Smart Citation